Raloxifene supports early fracture healing more than estrogen in ovariectomized rats - Stuermer, E. K.; Sehmisch, S.; Daub, F.; Komrakova, M.; Tezval, M.; Stuermer, K. M. (Osteologie, 2013)
Objectives: Most people suffering from osteoporosis are undiagnosed: the first osteopenic fracture strikes an untreated organism. Therefore implant fixation often fails and bone healing is disturbed. In this basic research project, we explore possibilities to improve the quality of the osteopenic bone immediately after a fracture to avoid these complications.Methods: Thirty-six female rats, which developed osteopenia within ten weeks duration after ovariectomy (OVX), underwent a standardized metaphyseal osteotomy with a bridging T-plate-fixation. After that rats were divided into three groups, which received soyfree food supplemented with raloxifene (R: 2.02 mg/d) or estradiol-17β-benzoate (E: 0.09 mg/d), orally, or soyfree food (SF) only. During fracture healing the rats were subcutaneously injected with fluorescent agents to help label and visualize the process of bone formation. Bones were analyzed using a three-point bending test, histological sections and microradiographs.Results: Raloxifene and estradiol have exerted anabolic effects on the trabecular bone. Both substances induced fracture healing mainly via endosteal callus formation (R: 2.08 ± 0.66 mm2, E: 2.02 ± 0.75 mm2 vs. SF: 1.78 ± 0.74 mm2). Due to early bridging and advanced fracture healing, less bone occurred in the later stages after application of test substances. The biomechanical features of the callus formations determined by the Yield load of R- (100.3 ± 28.4 N) were at the level of E-treated bone (93.8 ± 29.7 N) being higher in both comparing to the osteopenic bones (SF: 76.4 ± 18.8 N).Conclusions: Raloxifene and estrogen had supporting effects in the therapy of fractures of osteopenic bone. They improved not only the bone, but also the callus structure. The raloxifene- and estradiol-treatment enhanced the mechanical properties of the osteopenic bone, which probably lead to (micro) fracture risk reduction. Taking into account all the results there is an advantage for raloxifene; additionally its negative side effects detected in human settings, with respect to e. g. breast cancer propagation, are less than that of estrogens.
Keywords: Fracture healing; osteopenia; raloxifene; estrogen; bone